Exnovation of Low Value Care: a Decade of PSA Screening Practices - Bynum, Julie (J Am Geriatr Soc, 2018)
BACKGROUND: Reducing use of low-value services is a priority for improving quality and lowering cost of care. The release of trial evidence in 2009 showing low value for prostate-specific antigen (PSA) screening in asymptomatic men and the convergence of guidelines offers an opportunity to study how clinical practice evolves with mounting consensus about the low value of a service. OBJECTIVE: Examine PSA screening practice change across subgroups of men defined in guidelines and across regions, identifying factors associated with change in screening practices. DESIGN: Observational study using serial cross-sections, 2003 to 2013 SETTING: National fee-for-service Medicare PARTICIPANTS: Men age 68 and older eligible for prostate cancer screening MEASUREMENTS: Outcomes are national PSA screening practices among men age 68 and older from 2003–2013 and change in regional screening rates among men age 75 and older. RESULTS: The PSA screening rate among men age 68 and over was 17.2% in 2003, 22.3% in 2008, and 18.6% in 2013 (p<.001 for all differences); rates ended slightly lower than rates in 2003 only among men 80 and older. Racial disparities in screening became less pronounced over this period. Among men 75 and older, change in regional screening rates varied widely, with absolute rates growing by 15 per 100 enrollees in some areas and declining by the same amount in others. Areas with high social capital, a measure associated with diffusion of new ideas, were more likely to decline while malpractice intensity and managed care penetration had no impact. CONCLUSIONS: Studying Medicare enrollees over time, we found little reduction in PSA screening and even increases by race and in some regions. The heterogeneous changes across regions suggest consistent reduction in the use of low-value care may require change strategies that go beyond evidence and guidelines to include monitoring and feedback on performance.